2014
DOI: 10.4103/0974-9233.124110
|View full text |Cite
|
Sign up to set email alerts
|

Manual suture less small incision cataract surgery in patients with uveitic cataract

Abstract: Purpose:The purpose of this study is to evaluate the outcome of manual small incision cataract surgery (SICS) in eyes with uveitic cataract.Setting:Medical college hospital of the subcontinent.Design:Retrospective case series.Materials and Methods:In this retrospective study, patients who underwent SICS with posterior chamber intraocular lens implantation for uveitic cataract from 2006 to 2009 were evaluated. Patients with less than 3 months follow-up were excluded. Post-operative vision and complications were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…On the first postoperative day, there were more cases of corneal edema (12,17.1%) in the phacoemulsification group than in the SICS group (8,11.4%) (P = 0.046). The mean endothelial cell loss in these patients was 26.8% at 1 week and 31.4% at 6 months in the phacoemulsification group and 22.7% and 26.4% in the SICS group, respectively.…”
Section: Complicationsmentioning
confidence: 80%
See 1 more Smart Citation
“…On the first postoperative day, there were more cases of corneal edema (12,17.1%) in the phacoemulsification group than in the SICS group (8,11.4%) (P = 0.046). The mean endothelial cell loss in these patients was 26.8% at 1 week and 31.4% at 6 months in the phacoemulsification group and 22.7% and 26.4% in the SICS group, respectively.…”
Section: Complicationsmentioning
confidence: 80%
“…It requires minimal instrumentation and can be performed in rural and semirural settings as well. 7,8 However, the safety and efficacy of SICS in FHI has not been established. An extensive review of the literature did not reveal any published randomized controlled trials comparing phacoemulsification and manual SICS for FHI (MEDLINE search).…”
mentioning
confidence: 99%
“…The mSICS is preferred option by surgeons and could be performed in rural and semi-urban settings and in eye-camps. 15,16 It is preferred in high volume outreach camp, such as in low socio-economic communities in the developing countries, due to its cost effective, comparable visual outcome, while being non machine dependent. 16 The limitation of the present study was the best corrected visual acuity examination was heavily influenced by the condition of the posterior segment.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the rate of postoperative complications between phacoemulsification and manual SICS. In a retrospective study on 53 eyes in patients with uveitis Bhargava et al (2014) found manual SICS to be a safe procedure with predictably good visual outcome. Persistent uveitis, macular edema and PCO were the main factors affecting visual outcome.…”
Section: Discussionmentioning
confidence: 99%